Cord atrophy separates early primary progressive and relapsing remitting multiple sclerosis. Issue 9 (22nd June 2006) - Bieniek, M; Altmann, D R; Davies, G R; Ingle, G T; Rashid, W; Sastre-Garriga, J; Thompson, A J; Miller, D H
Abstract : Background and objective: The onset of multiple sclerosis is relapsing remitting or primary progressive. An improved understanding of the causes of early progressive disability in primary progressive multiple sclerosis (PPMS) could provide mechanistic targets for therapeutic intervention. Methods: Five magnetic resonance imaging (MRI) parameters that could potentially cause progressive disability were investigated in 43 patients with early PPMS and in 37 patients with early relapsing remitting multiple sclerosis (RRMS): atrophy in brain, both grey matter and white matter; intrinsic abnormality in brain, both grey matter and white matter (measured by the magnetisation transfer ratio (MTR)); and atrophy of the upper cervical spinal cord. Both groups were also compared with controls. Results: Patients with PPMS were older and more likely to be men. Both patient groups had atrophy of brain grey matter and white matter, and intrinsic abnormality in MTR of normal-appearing grey matter and white matter. Cord atrophy was present only in the PPMS (mean cord area: PPMS, 67.8 mm 2 ; RRMS, 72.7 mm 2 ; controls, 73.4 mm 2 ; p = 0.007). This was confirmed by multivariate analysis of all five MRI parameters, age and sex. Conclusion: Grey matter and white matter of the brain are abnormal in both early RRMS and PPMS, but cord atrophy is present only in PPMS. This is concordant with myelopathy being the usual clinical presentation of PPMS. Measurement of cord atrophy seems to be clinically relevant in PPMS treatment trials.